Naturlig föryngring av lövskogar i Örebro län - Carlsson, Lars (SLU/Dept. of Silviculture, 2005)
The Regional Forestry Board in Värmland- Örebro needs increased knowledge on silviculture in broad- leaved forests. This thesis is an inventory of naturally regenerated broad leaved forests, and the results from the inventory have been compared with The Regional Forestry Board's demands on regeneration results. The result of this inventory was that the regenerated sites were suitable for broad leaved trees, but only half the number of the stands fulfilled the demands of regeneration results of The Regional Forestry Board, mainly because of gaps in the stands. The gaps in the stands were mainly caused by lack of soil preparation and seed trees.